Safety and immunogenicity of the RTS, S/AS01 malaria vaccine in infants and children identified as HIV-infected during a randomized trial in sub-Saharan Africa. Issue 4 (22nd January 2020) - Otieno, Lucas; Guerra Mendoza, Yolanda; Adjei, Samuel; Agbenyega, Tsiri; Agnandji, Selidji Todagbe; Aide, Pedro; Akoo, Pauline; Ansong, Daniel; Asante, Kwaku Poku; Berkley, James A; Gesase, Samwel; Hamel, Mary J.; et al.
Highlights: The RTS, S/AS01 malaria vaccine was assessed in a phase 3 trial in sub-Saharan Africa. We evaluated the vaccine in a subset of children identified as HIV+ in this trial. The safety of RTS, S/AS01 in HIV+ children was similar to that of comparator vaccines. RTS, S/AS01 was immunogenic in HIV+ children. Antibody levels in HIV+ children were lower than in children with unknown HIV status. Abstract: Background: We assessed the safety and immunogenicity of the RTS, S/AS01 malaria vaccine in a subset of children identified as HIV-infected during a large phase III randomized controlled trial conducted in seven sub-Saharan African countries. Methods: Infants 6–12 weeks and children 5–17 months old were randomized to receive 4 RTS, S/AS01 doses (R3R group), 3 RTS, S/AS01 doses plus 1 comparator vaccine dose (R3C group), or 4 comparator vaccine doses (C3C group) at study months 0, 1, 2 and 20. Infants and children with WHO stage III/IV HIV disease were excluded but HIV testing was not routinely performed on all participants; our analyses included children identified as HIV-infected based on medical history or clinical suspicion and confirmed by polymerase chain reaction or antibody testing. Serious adverse events (SAEs) and anti-circumsporozoite (CS) antibodies were assessed. Results: Of 15459 children enrolled in the trial, at least 1953 were tested for HIV and 153 were confirmed as HIV-infected (R3R: 51; R3C: 54; C3C: 48). Among these children, SAEs were reported for 92.2% (95% CI: 81.1–97.8) in the R3R, 85.2% (72.9–93.4) in the R3C and 87.5% (74.8–95.3) in the C3C group over a median follow-up of 39.3, 39.4 and 38.3 months, respectively. Fifteen HIV-infected participants in each group (R3R: 29.4%, R3C: 27.8%, C3C: 31.3%) died during the study. No deaths were considered vaccination-related. In a matched case-control analysis, 1 month post dose 3 anti-CS geometric mean antibody concentrations were 193.3 EU/mL in RTS, S/AS01-vaccinated HIV-infected children and 491.5 EU/mL in RTS, S/AS01-vaccinated immunogenicity controls with unknown or negative HIV status (p = 0.0001). Conclusions: The safety profile of RTS, S/AS01 in HIV-infected children was comparable to that of the comparator (meningococcal or rabies) vaccines. RTS, S/AS01 was immunogenic in HIV-infected children but antibody concentrations were lower than in children with an unknown or negative HIV status. Clinical trial registration: ClinicalTrials.gov: NCT00866619.